An investigation of genetic variation of (Quercus. castaneafolia C. A. Mey) in Neka and Noor forest of Mazandarn using peroxides activities. - Shahla Reisi; Seyed Gholamali Jalali; Kambiz Espahbodi (تاکسونومی و بیوسیستماتیک, 2011)
In order to determine the within and between genetic variation of Caspian oak (Quercus. castanefolia) populations, Based on quantitative and qualitative peroxides activity, 50 trees were selected in 5 habitats in Neka and Noor forest of Mazandaran in Iran. Habitat were located from 170 to 1100 meter above see level. One-year-old branch samples of trees was prepared to enzyme extraction. Quantitative studies accomplished by UV spectrophotometer (in 530 NM wave lengths) and qualitative studies performed by poly acryl amid gel electrophoresis (PAGE). Based on quantitative studies results, the most peroxides activity related to midland habitats (Ladvije and Khoram Chamaz). According to isozyme bands grouping, all five habitats classified in three groups. Laei Pasand habitat (1100 meter a.s.l.) performed a single group. A cluster analysis of 50 trees performed 10 clusters. The most genetic distance had been seen between midland habitats and highland habitats. The minimal genetic distance related to some trees of lowland habitats and midland habiatats. Therefore elevation changes were great role in habitats classification. According to allelic diversity, and heterozygosis values (compared with foreign studies) genetic variation of Caspian oak was higher than the European oaks habitats, but within genetic variation of Caucasian oak habitats was more than it's between genetic variation.